The savior generals : how five great commanders saved wars that were lost, from ancient Greece to Iraq - Hanson, Victor Davis (Bloomsbury Press, 2013)
Traces the stories of Themistocles, Belisarius, William Tecumseh Sherman, Matthew Ridgway, and David Petraeus, evaluating their pivotal military roles and the controversies that marked their careers.